2012
DOI: 10.3758/s13414-012-0290-3
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of first- and second-order motion systems by perceptual learning

Abstract: Previous studies investigating transfer of perceptual learning between luminance-defined (LD) motion and texture-contrast-defined (CD) motion tasks have found little or no transfer from LD to CD motion tasks but nearly perfect transfer from CD to LD motion tasks. Here, we introduce a paradigm that yields a clean double dissociation: LD training yields no transfer to the CD task, but more interestingly, CD training yields no transfer to the LD task. Participants were trained in two variants of a global motion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…On the other hand, we also show that the learning effect is specific to second-order processing. This result, together with previously reported asymmetry of transfer of learning between first-and second-order stimuli (Chen, Qiu, Zhang, & Zhou, 2009;Chung et al, 2008;Petrov & Hayes, 2010;Vaina & Chubb, 2012), indicates that perceptual learning in first-and second-order processing may occur at different stages of visual processing.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…On the other hand, we also show that the learning effect is specific to second-order processing. This result, together with previously reported asymmetry of transfer of learning between first-and second-order stimuli (Chen, Qiu, Zhang, & Zhou, 2009;Chung et al, 2008;Petrov & Hayes, 2010;Vaina & Chubb, 2012), indicates that perceptual learning in first-and second-order processing may occur at different stages of visual processing.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, Chung, Li, and Levi (2008) trained observers with amblyopic vision to identify near-threshold luminancedefined (first-order) and contrast-defined (second-order) letters and found that the learning effect transferred from first-order to second-order tasks but not vice versa. Vaina and Chubb (2012) found no transfer between perceptual learning of luminance-defined (first-order) global motion and texture-contrast-defined (second-order) global motion tasks. Although the results on transfer of perceptual learning between first-and second-order processing are mixed, these previous studies suggest that first-and second-order perceptual learning might be at least partially independent.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…This was used to argue that the oscillation advantage for vection may have a preconscious origin. However, an alternative explanation could be that first- and second-order motion systems do not interact in global motion perception [46] [49] , although see [50] .…”
Section: Discussionmentioning
confidence: 99%
“…This makes the transfer of perceptual learning in one visual system to the other a likelihood. Indeed, some studies confirmed the existence of such transfers (Chen, et al, 2009;Chung, Li, & Levi, 2008b;Petrov & Hayes, 2010;Zanker, 1999;Schofield, Ledgeway, & Hutchinson, 2007; but see Vaina & Chubb, 2012). However, it remains an open question whether this transfer is asymmetric (unidirectional, i.e., only from first-order to second-order or only from second-order to first-order) or symmetric (bidirectional, i.e, from first-order to second-order and vice versa).…”
Section: + a T Bmentioning
confidence: 99%